Eksplorasi Kognitif Mahasiswa Calon Guru dalam Menyelesaikan Soal Matematika Open Ended - Sella Veronika; Reri Seprina Anggraini (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
This study aims to explore the cognitive skills of prospective mathematics teacher students in solving open-ended mathematical problems based on Bloom's taxonomy. Open-ended problems allow students to use various solution approaches, thereby requiring higher-order thinking skills. The study was conducted at IAIN Kerinci using a qualitative case study approach. The subjects consisted of 28 students from the Mathematics Education Study Program, with 6 selected for in-depth interviews. Data were collected through open-ended mathematical problem tests and interviews.The validity and reliability of the instruments were established through expert judgment and initial trials. The data were analyzed using thematic analysis, which involved data reduction, coding according to cognitive levels, theme categorization, and conclusion drawing. The findings indicate that the majority of students operated at lower cognitive levels, specifically (C1, C2, C3), with only a small number reaching higher levels such as (C4, C5, C6). Most students relied on procedural strategies based on memorization, with only a few demonstrating varied and exploratory strategies. This study indicates that students' higher-order thinking skills still need to be improved through learning approaches that encourage exploration, reflection, and open-ended problem solving. This study emphasizes the importance of developing mathematics education curricula and training prospective teachers, emphasizing the need for pedagogical interventions specifically designed to encourage the transition of cognitive skills from lower levels (C1-C2) to higher levels (C4-C6), so that prospective teachers are ready to facilitate critical thinking in their future classrooms.